PENINGKATAN KEMAMPUAN KOGNITIF MELALUI JOYFULL LEARNING MENGGUNAKAN GAME WORDWALL PADA PESERTA DIDIK KELOMPOK B TK KARTIKA IV-21 MADIUN - Astuti Widyarini, Dyah; Binti Rofikah, Ciah; Setyaningsih, Istiqomah; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study seeks to enhance the cognitive skills of Group B students at TK Kartika IV-21 Madiun by applying a joyful learning approach through the Wordwall game. The learning activities were structured to provide a stimulating and interactive environment, tailored to the developmental characteristics of young children. The study employed classroom action research implemented over two cycles, involving 19 students as participants. Findings indicate notable improvements in cognitive abilities, particularly in number recognition, sorting colors and shapes, and arranging simple patterns. Moreover, students demonstrated increased motivation, enthusiasm, and active engagement throughout the learning process. Consequently, Wordwall-based joyful learning proves to be an effective alternative strategy for fostering cognitive development in early childhood education within a sustainable and contextually integrated framework.